Microelectronics, Electromagnetics and Telecommunications Proceedings of the Fourth ICMEET 2018 - Panda, Ganapati; Satapathy, Suresh Chandra; Biswal, Birendra; Bansal, Ramesh (Lecture Notes in Electrical Engineering, 2019)
The book discusses the latest developments and outlines future trends in the fields of microelectronics, electromagnetics and telecommunication. It contains original research works presented at the International Conference on Microelectronics, Electromagnetics and Telecommunication (ICMEET 2018), organised by GVP College of Engineering (A), Andhra Pradesh, India. The respective papers were written by scientists, research scholars and practitioners from leading universities, engineering colleges and R&D institutes from all over the world, and share the latest breakthroughs in and promising solutions to the most important issues facing today's society.